Targeting Macrophages in Cancer: From Bench to Bedside - Poh, Ashleigh R.; Ernst, Matthias (Frontiers in Oncology, 2018)
Macrophages are a major component of the tumor microenvironment and orchestrate various aspects of immunity. Within tumors, macrophages can reversibly alter their endotype in response to environmental cues, including hypoxia and stimuli derived from other immune cells, as well as the extracellular matrix. Depending on their activation status, macrophages can exert dual influences on tumorigenesis by either antagonizing the cytotoxic activity immune cells, or by enhancing anti-tumor responses. In most solid cancers, increased infiltration with tumor-associated macrophages has long been associated with poor patient prognosis, highlighting their value as potential diagnostic and prognostic biomarkers in cancer. A number of macrophage-centred approaches to anti-cancer therapy have been investigated, and include strategies to block their tumor-promoting activities or exploit their anti-tumor effector functions. Integrating therapeutic strategies to target tumor-associated macrophages to complement conventional therapies has yielded promising results in pre-clinical trials, and warrants further investigation to determine its translational benefit in human cancer patients. In this review, we discuss the molecular mechanisms underlying the pro-tumorigenic programming of macrophages and provide a comprehensive update of macrophage-targeted therapies for the treatment of solid cancers.